Mineral and Bone Mass Changes During Pregnancy and Lactation - Oliveri, María Beatriz (2004)
During the past decade many factors have come together to producean explosive increase in investigations on bone and mineralmetabolism during pregnancy and lactation. Among some populations,frequent pregnancies and long lactation periods may leadto severe skeletal damage in the mother.1 For example, a case ofsevere after birth osteoporosis in a 30-y-old woman was describedin 1948 in the classic book by Albright and Reifenstein...